Ergonomic risk in the nursing professional: narrative review - Puicon Mejia, Mara Jemina (2022)
Objective: To determine the ergonomic risks to which nursing professionals are exposed. Method: Narrative bibliographic review. A bibliographic search of original articles published during 2011-2021 was carried out in the databases: VHL, ProQuest, PubMed, ScienceDirect, SciELO and Redalyc, using the descriptors: ergonomics, risk, environmental risks and nursing, in languages: Spanish, Portuguese and English, an advanced search was carried out and then compliance with the exclusion and inclusion criteria was verified, finally it was validated through The application of methodological guides, obtaining a sample of 20 documents. Main results: the selected articles were qualitative, quantitative and mixed; following the analysis of the content were grouped into central categories: injuries and psychological repercussions; characteristics of the working environment and physical loads encompassing third-level categories: load handling, repetitive movements and forced postures; finally, the thermal environment, noise and lighting. Overall conclusion: There is a higher prevalence in ergonomic risks concerning temporal ergonomics, these are triggered by the lack of organization during work; while the risks in geometric ergonomics are due to the lack of adequate strategies and measures in the face of constant handling of loads and repetitive movements, finally the risks in environmental ergonomics generate dissatisfaction with the thermal environment, lighting and noise. there is a shortage of research in the area of teaching, in addition to qualitative and mixed studies. The implementation of education programs, prevention strategies and the necessary equipment and supplies are urgent.